Safety and effects of transcranial direct current stimulation on hand function in preschool children with hemiplegic cerebral palsy: A pilot study - He, Wenjie; Huang, Yuan; He, Lu; Liu, Liru; Zeng, Peishan; Qiu, Huiying; Wang, Xiaoyue; Zhou, Hongyu; Chen, Zhaofang; Xu, Yi; Zhao, Jingyi; Wang, Wenda; et al. (Frontiers in Behavioral Neuroscience, 2022)
Transcranial direct current stimulation (tDCS) has shown a promising prospect in improving function and spasticity in school-aged children with cerebral palsy, but little is known in preschool children. The aim of this study was to explore the safety and effects of tDCS on hand function in preschool children (aged 3-6 years) with hemiplegic cerebral palsy (HCP). We designed a crossover, single-blind, sham-controlled study in 30 preschool children with HCP, who were recruited to receive one session of sham and one session of active anodal tDCS (1.5 mA, 20 minutes) on the primary motor cortex of the affected hemisphere, with a 24-hour interval between the two sessions. Questionnaire was completed by each participant and their attendants immediately, 90 minutes and 24 hours after each session to monitor common adverse events of tDCS, such as skin irritation, skin erythema, burning sensation, headache, dizziness, etc. Box and Block Test, Selective Control of the Upper Extremity Scale, Modified Ashworth Scale, and Melbourne Assessment 2 were conducted at baseline, immediately and 90 minutes after each session. No severe adverse event occurred during the study and only a few of them felt transient and slight discomfort. Results also showed that all participants performed better at Box and Block Test of the hemiplegic hand immediately after a single anodal tDCS (P<0.05) and this improvement lasted at least 90 minutes and more than 24 hours. However, there was no significant improvement in Selective Control of the Upper Extremity Scale of both hands, Box and Block Test of the nonhemiplegic hand, Modified Ashworth Scale and Melbourne Assessment 2 of the hemiplegic upper limb (P>0.05). Shortly, this study supported the safety and effects of a single anodal tDCS on improving the manual dexterity of the hemiplegic hand for preschool children with HCP. Further researches with larger samples about the optimal dose and treatment cycle of tDCS for preschool children with HCP are warranted. This study gained the approval of ethics committee of the organization and was registered at chictr.org (ChiCTR2000031141).